Измерение длительности одиночного импульса методом пакетного совпадения - Кадацкая, О. И. (ХНУРЭ, 2007)
Предложен метод измерения длительности одиночного импульса с разрешающей способностью, определяемой разностно-периодной мерой, которая может быть на порядок ниже, нежели длительности импульсов, определяющих пакет совпадений. Оценена точность предложенного метода. The offered method of measurement of the single pulse with resolving power duration, defimed with difference-period measure, which can be of the order below than pulse duration, defining the coincidences package. The accuracy of the offered method is estimated. The method allows to raise the accuracy of the measurement two orders of magnitude, reduces requirements to element base.
Keywords: одиночный импульс; метод пакетного совпадения